Influência das águas da Bacia Hidrográfica Pirangi na balneabilidade das praias de Pirangi, nos municípios de Nísia Floresta e Parnamirim Rio Grande do Norte, Brasil - Medeiros, Juçara Ramalho de (2009)
The Pirangi beach is located in the eastern coastline of Rio Grande do Norte state, in the municipality of Parnamirim and Nísia Floresta. In it flow into Pirangi Watershed (PW), whose water receives large amounts of pollutants, mainly domestic and industrial sewage from districts where pass the rivers that consist it, compromising, thus, the bathing water quality of the Pirangi beach. Bearing in mind the importance of water sanitary quality to ensure an environment that no present risk to the bathers s health, this work had as main objective to assess the influence of the PW s waters in the bathing water quality of the Pirangi beaches. To that end, were made collections of water in the beaches and in the rivers with the intention of quantify the fecal contamination indicators thermotolerant coliforms and enterococci, to then classify the conditions of bathing water quality according with the CONAMA Resolution number 274 of 2000. For the purposes greater knowledge about the health conditions of the Beaches Pirangi and about the influence the PW s waters exert on it, was done parallely to the study of the water quality, an investigation of the sand sanitary quality. Furthermore, it was made an evaluation of the PW s Water Quality through Water Quality Index (WQI). Starting from the results obtained in the research present was possible to verify, among other aspects, that the entry of the PW s waters in the Pirangi beaches exerts direct influence in the bathing water quality of the same ones, being the North Pirangi beach (point tracking PA-02) the most influenced. There was noticed also a significant reduction in the conditions of bathing water quality of the beaches in the rainy season. However, the precariousness do sewerage system of the Natal metropolitan region and the absence of a right system of treatment an final disposal of domestic sewage and industrial are the main factors responsi le for deterioration of the PW s Water Quality, and as a consequence, compromising the bathing water quality of the Pirangi beaches